2011
DOI: 10.1177/070674371105600103
|View full text |Cite|
|
Sign up to set email alerts
|

What We Have Learned about Electroconvulsive Therapy and its Relevance for the Practising Psychiatrist

Abstract: Clinical Implications• ECT is highly efficacious for the treatment of major depressive disorder, bipolar disorder, and catatonia.• The presence of psychotic symptoms, suicidal thoughts, or catatonic signs should prompt the clinician to consider ECT earlier in the treatment course.• Current standards of ECT practice have been able to reduce side effects. Limitations• Our review is narrative and limited to literature with a clear relevance for the referring psychiatrist.• More studies are needed on continuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 68 publications
(84 reference statements)
0
25
0
Order By: Relevance
“…After the ECT course, patients who had responded were advised to start treatment with continuation ECT (for instance one ECT per month for half a year), the others were advised treatment with an antidepressant. Naturalistic studies have found that 50 % or more of remitted patients have a relapse of depression within 6-12 months of discontinuing acute ECT, so psychological and biological continuation treatment is indicated (Sienaert, 2011). Continuation ECT is at least equally effective in avoiding relapse as continued psychopharmacological treatment (Smith et al, 2010).…”
Section: Ectmentioning
confidence: 99%
“…After the ECT course, patients who had responded were advised to start treatment with continuation ECT (for instance one ECT per month for half a year), the others were advised treatment with an antidepressant. Naturalistic studies have found that 50 % or more of remitted patients have a relapse of depression within 6-12 months of discontinuing acute ECT, so psychological and biological continuation treatment is indicated (Sienaert, 2011). Continuation ECT is at least equally effective in avoiding relapse as continued psychopharmacological treatment (Smith et al, 2010).…”
Section: Ectmentioning
confidence: 99%
“…However, despite its proven efficacy and safety, ECT is often applied as a last resort [6,7]. There are three main factors precluding a broader application of ECT.…”
Section: Introductionmentioning
confidence: 99%
“…First, it can be difficult to obtain written informed consent from an agitated and irritable patient; second, concerns often arise with regard to stigmatization of the intervention, and third, transient cognitive impairments are possible. As a result, ECT is considered as the third line in the treatment of BPD [5,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Individuals who fail to respond to more than two psychopharmacological treatments are suffering from treatment-resistant depression (TRD). Electroconvulsive therapy (ECT) has demonstrated efficacy for TRD patients (Sienaert, 2011), but it is often accompanied by memory disturbances and relatively high relapse rates (Rasmussen, 2002). Other treatments such as transcranial magnetic stimulation (rTMS) or vagal nerve stimulation (VNS) appear to have limited efficacy (Kennedy and Giacobbe, 2007).…”
Section: Introductionmentioning
confidence: 99%